2021
DOI: 10.1007/s10653-021-01149-w
|View full text |Cite
|
Sign up to set email alerts
|

Spatiotemporal variability of nitrogen dioxide (NO2) pollution in Manchester (UK) city centre (2017–2018) using a fine spatial scale single-NOx diffusion tube network

Abstract: Nitrogen dioxide (NO2) is linked to poor air quality and severe human health impacts, including respiratory and cardiovascular diseases and being responsible annually for approximately 23,500 premature deaths in the UK. Automated air quality monitoring stations continuously record pollutants in urban environments but are restricted in number (need for electricity, maintenance and trained operators), only record air quality proximal to their location and cannot document variability of airborne pollutants at fin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 65 publications
2
11
0
Order By: Relevance
“…The effects of meteorology on the concentration and dispersion of nitrogen dioxide have been revealed in many studies. As in our case study, some of them confirm the absence of a significant difference in average NO 2 concentration between the different study periods [72,73]. On the other hand, other studies have revealed a periodic variability attributed mainly to differences in the meteorological profiles of these periods [74,75].…”
Section: Discussionsupporting
confidence: 88%
“…The effects of meteorology on the concentration and dispersion of nitrogen dioxide have been revealed in many studies. As in our case study, some of them confirm the absence of a significant difference in average NO 2 concentration between the different study periods [72,73]. On the other hand, other studies have revealed a periodic variability attributed mainly to differences in the meteorological profiles of these periods [74,75].…”
Section: Discussionsupporting
confidence: 88%
“…nitrate (NO 3 − ) and ammonium (NH 4 + ). Accordingly, different nitrate (NO 3 − ) and ammonium (NH 4 + ) concentrations have been reported in X. parietina samples across Manchester (Niepsch et al 2021b), suggesting site-specific and diverse sources; e.g., from vehicular, domestic and industrial emissions that potentially impacted on lichen wt% N recorded by this study (further discussed in "Lichen nitrogen stableisotope ratios (δ 15 N)"; Fig. 8).…”
Section: Spatial Variability Of Carbon Nitrogen and Sulfur Contents I...mentioning
confidence: 61%
“…Indeed, lichen enrichment in 15 N was recorded at sampling locations in proximity to the highlytrafficked Mancunian Way with approximately 30,000 vehicles passing daily (DfT 2017). Comparably, δ 15 N was positively correlated with passively-derived NO 2 concentrations by Niepsch et al (2021a) in X. parietina (Pearson's r = 0.54, p < 0.01) and Physcia spp. (Pearson's r = 0.37, p < 0.01; Table S6), consequently suggesting a major NO x -related influence in Manchester.…”
Section: Lichen Nitrogen Stable-isotope Ratios (δ 15 N)mentioning
confidence: 92%
See 1 more Smart Citation
“…However, NH4 + concentrations were elevated in both environments (no statistically significant difference), although likely linked to different sources, whereas NO3concentrations are potentially related to increased NOx emissions in the urban environment. Comparably, Niepsch et al (2021) reported elevated NO2 concentrations across Manchester 76 .…”
Section: Optimised Extraction Methods To Compare Rural and Urban Lich...mentioning
confidence: 90%